Electrospun Nanofibers: Uniform Luminous Perovskite Nanofibers with Color‐Tunability and Improved Stability Prepared by One‐Step Core/Shell Electrospinning (Small 22/2018). Issue 22 (28th May 2018) - Tsai, Ping‐Chun; Chen, Jung‐Yao; Ercan, Ender; Chueh, Chu‐Chen; Tung, Shih‐Huang; Chen, Wen‐Chang
Abstract : In article number1704379, Shih‐Huang Tung, Wen‐Chang Chen, and co‐workers demonstrate the preparation of uniform luminous perovskite nanofibers by a one‐step core/shell electrospinning technique. The luminous electrospun nanofibers possess wide color‐tunability by varying the perovskite composition. Also, the grain size of the formed perovskite nanocrystals is largely controlled by the perovskite precursor stoichiometry and the polymer solution concentration.